Peranan Dinas Pengendalian Penduduk dan Keluarga Berencana dalam Pengendalian Pertumbuhan Penduduk - Larasati Larasati; Indra Muda; Beby Masitho Batubara; Agung Suharyanto (Universitas Medan Area, 2018)
This study aims to find out how the role of the Family Planning Population Control Office, the determination of policies and programs in controlling the population growth rate in Medan City, besides that the author also wants to know the factors that prevent the Population and Family Planning Control Office from controlling growth residents in Medan City. The research technique used is a qualitative research method with interviews and observations. The research subject taking technique is using purposive and snowball techniques. From this technique, informants obtained, consisting of the Head of the Population and Family Planning Control Office, Head of the Family Planning Division, Head of Extension and Penggerak, Head of Resilience, Head of Population Control, Family Planning Field Extension, and the community who participated in the Family program. Planning or those who do not take part in the Family Planning program. Based on the research conducted, it was found several findings that the Office of Population and Family Planning Control has a role in suppressing population growth which includes coordination with government, community and private institutions in family planning activities, conducting family planning counseling, installing contraceptives and post-installation contraception. Obstacles in controlling population growth, namely the lack of skilled technical personnel, inadequate infrastructure, the influence of culture and the level of education of the community also become obstacles to DP2KB in carrying out their duties and functions.